الإلهة آناهيتا دراسة في التطور التاريخي لعبادتها - سمار سعد عبود (Journal of College of Education, 2018)
This study sheds light on the goddess Anahita, the goddess of ancient Iranian water and fertility, in the light of the texts of Avesta, so we referred to her name and the origin of her worship, and we explained the total meaning of her name in its various forms, and the meaning of this name. We discussed the origins of her worship and gave a historical presentation of the development of her worship in the ancient Iranian ages (the Medi, the Achumini, the Saluki, the Feather and the Sasani). The study reviewed the most important temples.